"Sometimes it feels like thinking in syrup" – the experience of losing sense of self in those with young onset dementia. Issue 1 (1st January 2020) - Busted, Laila Mohrsen; Nielsen, Dorthe S; Birkelund, Regner
ABSTRACT: Purpose : To explore and describe the experience of people having young-onset dementia. Methods : This was a qualitative study that used semi-structured interviews to collect data from nine persons with young-onset dementia (aged 47–65; five men and four women). Data were collected in the spring of 2018. All interviews were conducted at the participants' choice and in their own homes by one interviewer. The collected data were analysed using the six-stage process of reflexive thematic analysis model. Results : The analysis revealed three themes: Dementia causing loss of control over oneself; becoming a burden to the family while sense of self disappears; and fearing a humiliating future. Conclusions : The experience of having and living with young onset dementia affected the persons' thoughts and memory and was experienced through the persons' loss of personality and sense of self. Thoughts about the future were associated with fear, and the risk of changing their personalities to something different from the one which they had experienced as humiliating throughout most of their lives.